INTEGRATING SNOWFLAKE AND AI FOR CLOUD-BASED DATA WAREHOUSING IN OIL & GAS OPERATIONS - Nihitha Sallapalli (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores the transformative integration of Snowflake and artificial intelligence technologies in cloud-based data warehousing for oil and gas operations. The article examines how this technological convergence addresses the industry's mounting challenges in managing vast data volumes generated from exploration, production, and operational activities. The investigation encompasses several key areas: scalable cloud infrastructure implementation, real-time processing capabilities through autonomic coordination systems, AI-driven predictive analytics, comprehensive data integration architectures, AI-powered decision support systems, and robust security and governance frameworks. The article analyzes how these integrated solutions enhance operational efficiency, reduce costs, improve decision-making accuracy, and strengthen security measures. Through detailed examination of current implementations and industry case studies, the article demonstrates how this technological integration is revolutionizing traditional operational paradigms while enabling more sustainable and efficient energy production practices. The findings highlight the significant impact of these integrated solutions on operational excellence, risk management, and environmental sustainability in the oil and gas sector.